The interface between nurse and patient in health care: exploring the use of emotional labour among nurses in Mthatha - Maqabuka, Qawekzi (Rhodes University, Faculty of Humanities, Department of Sociology, 2016)
In exploring the use of emotional labour among nurses within the nurse/patient relationship, this study employed the conceptual framework of 'emotional labour' associated with Arlie Hochschild-as a means of examining the "nature" of the nurse patient interface, including the dynamics, challenges and intricacies that shape this relationship of care. The portrayal of emotional care offered to patients dealing with suffering and illness by nurses as an entirely natural activity for women is related to the devaluation of emotional labour. The focus of this study is how nurses manage their emotional involvement with patients to provide quality services. The study was conducted in Mthatha in the former Transkei in the Eastern Cape Province with nurses who worked St Mary's Life Group and the Nelson Mandela Academic Hospital. A qualitative research design and qualitative ethnographic research methodology was chosen as suitable for answering the research question. Data was collected using semi-structured interviews and a focus group, and transcribed verbatim. Data analysis included identifying consistent emotional labour themes in the responses. The study's main findings revealed that emotional labour strategies of surface acting and deep acting were utilised as a means of meeting organisational rules established by management of the two health care institutions that were investigated. Nurses understood that only desirable traits like include friendliness, smiling and proving a calming environment for patients should be exhibited. It was revealed that nurses often used sentimental work and emotion work in performing their tasks as this made their work easier. Lastly, the research revealed that external factors like overcrowding and shortages in personnel, accompanied by the emotional demands on nurses' work has adverse effect on nurses work environment. The dissertation has contributed to the limited body of knowledge about emotional labour in the South African context and the lived experiences of nurses deploying their labour to patients.
Keywords: Uncatalogued